Miscarriage: types, diagnosis, treatment, prevention and aftercare - Prager, Sarah (Henry Stewart Talks, 2024)
Types of miscarriage, Early pregnancy loss (EPL), Expectant management, Medication management, Misoprostol, Mifepristone, Uterine aspiration management, Paracervical block, MIST trial, Counseling, Miscarriage prevention